2019
DOI: 10.3390/nu11010176
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Mitigates D-galactose-Induced Brain Aging by Increasing Hippocampal Neurogenesis and Improving Memory Function

Abstract: Ascorbic acid is essential for normal brain development and homeostasis. However, the effect of ascorbic acid on adult brain aging has not been determined. Long-term treatment with high levels of D-galactose (D-gal) induces brain aging by accumulated oxidative stress. In the present study, mice were subcutaneously administered with D-gal (150 mg/kg/day) for 10 weeks; from the seventh week, ascorbic acid (150 mg/kg/day) was orally co-administered for four weeks. Although D-gal administration alone reduced hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 54 publications
(80 reference statements)
8
42
0
Order By: Relevance
“…D-gal impaired antioxidant enzyme activities and increased pro-inflammatory cytokines also decreases cell proliferation [14]. Moreover, a study of neuronal cell survival using BrdU and NeuN double-staining reveal that D-gal decreases neuronal cell survival by inducing oxidative damage and inflammation [47]. In this study, neurogenesis in the group given chrysin at 10 and 30 mg/kg did not differ from that in the vehicle group.…”
Section: Discussionmentioning
confidence: 47%
“…D-gal impaired antioxidant enzyme activities and increased pro-inflammatory cytokines also decreases cell proliferation [14]. Moreover, a study of neuronal cell survival using BrdU and NeuN double-staining reveal that D-gal decreases neuronal cell survival by inducing oxidative damage and inflammation [47]. In this study, neurogenesis in the group given chrysin at 10 and 30 mg/kg did not differ from that in the vehicle group.…”
Section: Discussionmentioning
confidence: 47%
“…Physiologically, OPN promotes the expression of pro-survival genes via nuclear factor kappa-b (NF- K B) [53]. BDNF is the target gene of NF- K B. Pb-induced reduction of BDNF was observed in our present and previous studies, and ascorbic acid was shown to increase the expression of BDNF [20,24]. Along with the positive effect of ascorbic acid on BDNF expression, ascorbic acid is vital for neuronal differentiation and development, and myelin formation [54].…”
Section: Discussionmentioning
confidence: 56%
“…For histological evaluation, the procedures for Nissl staining and immunohistochemistry were used, as described in our previous studies [22,24]. Briefly, the remaining 12 offspring ( n = 12 per group) were anesthetized by urethane on PND21 and perfused transcardially with heparinized phosphate-buffered saline (PBS; 0.1 M, pH 7.4), followed by fixative (4% paraformaldehyde in 0.1 M phosphate buffer, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…33 Oxidative stress and microglial activation have been linked with various neurological and psychiatric disorders (Koga et al, 2019). 33 Vitamin C has also been shown to improve oxidative stress and neurogenesis in the hippocampus of rat model of ageing (Khalil et al, 2011;Nam et al, 2019). 16,34 All the reports suggest that the substances present in Tualang honey have beneficial effects on neurogenesis and have the potential to inhibit mitigate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%